Music and the Cultural Production of Scale - Dodds, Phil (Springer Nature, 2023)
This open access book shows how geographical scales are made through music. Scales are sets of spatial frames, abstractions or categories that denote the size, proportion, level, extent or hierarchical relations of phenomena. They are neither natural nor neutral but actively produced, with real political effects. But what role do cultural practices play in the production of scale? Phil Dodds addresses this question by focusing on music, arguing that music scholarship has both most to gain from and most to offer to a fuller conceptualisation of how geographical scale is culturally produced. Dodds suggests that music scholars should treat scales as open questions, and as phenomena potentially made throughmusical practices, rather than as stable categories for framing other arguments about, say, 'local' or 'global' music. He analyses how the meaning of 'the local' is affected by the aesthetics of popular music, and how the relationship between the particular and the general is fused through common musical conventions. Music and the Cultural Production of Scale explores diverse musical examples - including Janelle Monáe's concept albums, key tracks in the grime genre, protest songs at environmental and anti-fascist demonstrations, and nineteenth-century colonial hymn-singing - to demonstrate how we already live in a world whose scales are made by music. The book also shows that music has the potential to produce a world scaled otherwise.